2019
DOI: 10.1016/j.cpr.2019.05.001
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between acceptance of cancer and distress: A meta-analytic review

Abstract: Acceptance of cancer has long been recognized as playing a critical role in psychological adjustment to the illness, but its associations with distress outcomes have not been quantitatively reviewed. Informed by coping theory and third wave conceptualizations of acceptance, we first propose an integrated model of acceptance of cancer. Then we examine the strength of the relationships between acceptance of cancer and general and cancer-specific distress in cancer patients and potential moderators of these relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
75
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(88 citation statements)
references
References 104 publications
8
75
0
5
Order By: Relevance
“…For instance, some authors have found that coping strategies such as acceptance, positive reappraisal and seeking social support are associated with higher adaptation, well-being and quality of life in cancer. [ 13 15 ] On the contrary, disadaptive coping strategies such as self-blame, avoidance and negation are related to poorer mental health outcomes. [ 16 , 17 ]…”
Section: Introductionmentioning
confidence: 99%
“…For instance, some authors have found that coping strategies such as acceptance, positive reappraisal and seeking social support are associated with higher adaptation, well-being and quality of life in cancer. [ 13 15 ] On the contrary, disadaptive coping strategies such as self-blame, avoidance and negation are related to poorer mental health outcomes. [ 16 , 17 ]…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have indicated that, in the case of patients suffering severe breathlessness, their family caregivers report fewer positive, caring experiences than family caregivers of other types of patients [30]. Also, the family caregiver's depression level is particularly affected by how long the caregiving tasks have been performed and the severity of the d [31,32]. Finally, numerous studies have shown how family caregivers of patients with a long duration progressive illness such as COPD present a greater risk of problems concerning their mental or physical health, emotional distress, and an increase in mortality [4,33].…”
Section: Introductionmentioning
confidence: 99%
“…Scientific literature shows that there is a close link between patient's approach to cancer and the feeling of pain, or even the chance of survival. [38][39][40] Therefore, providing patients with psychological help of clinical psychologists can bring benefits both to patients and healthcare systems.…”
Section: Discussionmentioning
confidence: 99%